Role of ultrasound for assessment of psoriatic arthritis patients with fibromyalgia. Issue 12 (2nd July 2021) - Polachek, Ari; Furer, Victoria; Zureik, Mirna; Nevo, Sharon; Mendel, Liran; Levartovsky, David; Wollman, Jonathan; Aloush, Valerie; Tzemach, Reut; Elalouf, Ofir; Anouk, Marina; Berman, Mark; et al.
Abstract : Objective: To investigate whether ultrasonography (US), as an objective imaging modality, can optimise the evaluation of disease activity in psoriatic arthritis (PsA) patients with concomitant fibromyalgia syndrome (FMS). Methods: The study population included 156 consecutive PsA patients who were recruited prospectively and fulfilled the ClASsification criteria for Psoriatic ARthritis criteria. The patients underwent complete clinical evaluation including assessment of fulfilment of the 2016 fibromyalgia classification criteria. All of the patients underwent US evaluation including 52 joints, 40 tendons and 14 entheses. The US score was based on the summation of a semiquantitative score (including synovitis, tenosynovitis and enthesitis). Scoring was performed by a sonographer blinded to the clinical data. Spearman's correlation coefficient and multivariate linear regression models were used to examine the association of FMS with clinical and the US scores. Results: Forty-two patients (26.9%) with coexisting PsA and FMS were compared with 114 (73.1%) PsA patients without FMS. Patients with PsA and FMS had significantly increased scores for clinical composite indices, including non-Minimal Disease Activity, Composite Psoriatic Disease Activity Index (CPDAI), Disease Activity for Psoriatic Arthritis (DAPSA) and Psoriatic Arthritis Disease Activity Score (PASDAS) (p<0.001). In contrast, the total US score and its subcategories were similar for those with and without FMS. The total US score significantly correlated with CPDAI, DAPSA and PASDAS (p<0.001) in the PsA without FMS but not in the PsA with FMS group. FMS was significantly associated with higher clinical scores (p<0.001) but not with the US score (multivariable linear regression models). Conclusions: US has significantly greater value than composite clinical scores in the assessment of disease activity in PsA patients with FMS.